Pengaruh Corporate Governance terhadap Penghindaran Pajak pada Perusahaan Perbankan Periode 2018-2020 - Adiwiratna, Paras Surya; Lawita, Florencia Irena (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
This study is aimed at knowing the influence of corporate governance on tax avoidance assessed with an effective tax rate (ETR). The size of the board of commissioners, audit committee, managerial ownership and institutional ownership are used as elements in corporate governance to be tested in research. The sample was determined by purposive sampling which found 32 banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2020. The study used secondary data as database. The research analysis method used is a multiple regression analysis method and is processed using SPSS 25. The results showed that the size of the board of commissioner had a negative effect on tax avoidance. Instituional ownership had a positive effect on tax avoidance. The audit committee and managerial ownership cannot influence tax avoidance